Verapamil Ameliorates Hepatic Metaflammation by Inhibiting Thioredoxin-Interacting Protein/NLRP3 Pathways - Zhou, Feng; Zhang, Ying; Chen, Jing; Hu, Yimeng; Xu, Yancheng (Frontiers in Endocrinology, 2018)
Activation of thioredoxin-interacting protein(TXNIP)/nod-like receptor protein 3 (NLRP3) inflammasome plays a critical role in pathogenesis of non-alcoholic fatty liver disease. This study investigated the protective effects of verapamil on hepatic metaflammation in a rodent model of high-fat(HF) diet-induced obesity(DIO). DIO was induced in a subset of mice provided with HF diet(45% kcal fat). After 10 weeks of HF diet, verapamil was administered by intraperitoneal injection. The experimental groups included the following: 1) normal diet group, 2)normal diet + treatment with verapamil (VER) group, 3)HF control group,4)HF+VER(25mg/kg/day) group. After 1 week of each treatment, blood and liver tissues were collected, and glucose control, serum triglyceride(TG) level, inflammation and TXNIP/NLRP3 inflammasome were analysed. Verapamil administration caused no alteration in food intake. HF diet impaired glucose control and increased body weight and serum TG levels. Hepatic inflammation was aggravated in HF-fed mice, as demonstrated by increased levels of pro-inflammatory markers interleukin-1β(IL-1β) and IL-18 in the liver. On the other hand, verapamil administration significantly improved glucose control, body weight and serum TG levels. Verapamil treatment also reduced pro-inflammatory marker levels. These improvements were accompanied by alterations in activation of TXNIP/NLRP3 inflammasome. The observed results demonstrate that verapamil ameliorates hepatic metaflammation by inhibiting TXNIP/NLRP3 pathways.